Fabrication of hollow fibrous nanosilica with large pore channels. Issue 89 (19th October 2022) - Tran, Ngoc Minh; Doan, Thang Cao; Yoo, Hyojong
Abstract : Selective self-etching of dendritic fibrous nanosilica (DFNS): fabrication of hollow fibrous nanosilica (HFNS) with high specific surface area and large pore channels, and utilization as a robust support for the growth of gold nanoparticles. Abstract : The fabrication of hollow mesoporous nanosilica with well-defined structural features for optimizing the integration of functional components is a challenge. Herein, we report a facile preparation of hollow fibrous nanosilica (HFNS) with high specific surface area (666 m 2 g −1 ), fiber-like mesoporous architectures in the inner and outer shells, and large pore channels (16.22 nm) via selective self-etching of dendritic fibrous nanosilica in an aqueous medium. The specific surface area and pore diameter increased significantly after the formation of a cavity in the center, resulting in HFNS. The HFNS can serve as a robust support for the controllable growth of gold nanoparticles with maximum catalytic performance for 4-nitrophenol reduction.